The Magic Values of Pacu Jalur Tradition in the Perception of Society of Kenegerian Kari Kuantan Singingi - Sri Chairani; Febri Haswan; Helpi Nopriandi (Budapest International Research and Critics University, 2023)
The magic values is closely related to the level of society understanding with their religion. The aim of this research to find out the magic values in pacu jalur tradition and to find out the perception of society toward magic values of pacu jalur tradition. This research used qualitative method. The result concluded that many processes of making the jalur, there are the magic values in it. In every process, the magic values includes the tool, the mantra, the ritual, and the shaman. The perception of society towards magic values is various. It can be showed that there are some of society is believe towards magic values of pacu jalur, due to the mantra from dukun jalur or the shaman still mention the name of Allah and its not contrary with Islamic teachings, but they didn’t agree that magic as determiner of the race. Some society believe and agree that magic is important in pacu jalur tradition. But some of society is not believe towards magic values because its contrary with Islamic teaching and it includes polytheism. It can be shown by the shaman when he said the mantra in processing pacu jalur makings. The shaman ask mambang (kind of the spirit) in helping pacu jalur makings until finish and participate in event of pacu jalur. The deeds is opposite with Islamic teaching, and it will be syirik because believe another beside believe in Allah. Another perception of society towards magic values is neutral, because they have sense of indifference.